Women and Power at the French Court, 1483-1563 - Broomhall, Susan (Book collections on Project MUSE., 2018)
This book explores the ways in which a range of women-as consorts, regents, mistresses, factional power players, attendants at court, or as objects of courtly patronage-wielded power in order to advance individual, familial, and factional agendas in the early sixteenth-century French court. Spring boarding from the burgeoning scholarship of gender, the political, and power in early modern Europe, the book provides a perspective from the French court, from the reigns of Charles VIII to Henri II, a time at which the French court was a glittering centre of culture and which women are understood to have played increasingly important roles. Cross-disciplinary in its perspectives, these essays by historians, art and literary scholars cohesively investigate the dynamic operations of gendered power in political acts, recognised status as queens and regents, ritualised behaviors such as gift-giving, educational coteries, courtly household organisation, and social networking, literary and artistic patronage, female authorship, and epistolary strategies.